2021
DOI: 10.1016/j.jds.2020.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Heat-cured poly(methyl methacrylate) resin incorporated with different food preservatives as an anti-microbial denture base material

Abstract: Background/purpose The colonization of microorganisms onto denture bases is one common problem that can contribute to oral diseases. Herein, three food preservatives, including zinc oxide, potassium sorbate, and sodium metabisulfite were introduced as anti-microbial additives into a heat-polymerized poly(methyl methacrylate) (PMMA). Materials and methods Relative microbial reductions of the modified PMMA resins against Staphylococcus aureus , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
(27 reference statements)
1
4
0
1
Order By: Relevance
“…Notably, although SPA chains have been grafted onto the UiO-66 particles, the particle size of UiO-66-SPA is only about one-third of that of UiO-66. This is mainly due to the excellent dispersity of UiO-66-SPA nanoparticles through the electrostatic repulsion between the negatively charged SPA chains, 39,52,53 which is similar to the results reported previously. 46 3.2.…”
Section: Resultssupporting
confidence: 90%
“…Notably, although SPA chains have been grafted onto the UiO-66 particles, the particle size of UiO-66-SPA is only about one-third of that of UiO-66. This is mainly due to the excellent dispersity of UiO-66-SPA nanoparticles through the electrostatic repulsion between the negatively charged SPA chains, 39,52,53 which is similar to the results reported previously. 46 3.2.…”
Section: Resultssupporting
confidence: 90%
“…Disulfide bonds in protein structures can be broken by these substances, killing enzymes, and causing cellular damage. Therefore, it has been demonstrated that these effects of food preservatives on the denture base also have antibacterial capabilities on the denture base materials [ 39 ].…”
Section: Contemporary Modification On Denture Base Materialsmentioning
confidence: 99%
“…Poly(methyl methacrylate) (PMMA) resins are clinically used in prosthodontics in full and partial denture production for decades [1][2][3][4]. Despite the fact that there are many advantages of these materials, such as ease of laboratory processing, polishability, appropriate physicochemical properties, and no smell or taste after polymerization, the issues of microporosity and thus water absorption and susceptibility to microbial growth are still challenges in considering this material as ideal for removable prosthetic devices [5][6][7][8]. The appropriate composition of PMMA intended for the fabrication of dentures allows for satisfactory aesthetic effects not only in terms of artificial dentition, but also the so-called pink aesthetics, i.e., the color of the denture plate imitating atrophied soft tissues in the oral cavity and designed to distribute the chewing forces over a larger surface of the toothless prosthetic foundation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Statistically insignificant difference in post hoc Conover-Iman with comparison to ADW, 2 statistically insignificant difference in post hoc Conover-Iman with comparison to ACO,3 statistically insignificant difference in post hoc Conover-Iman with comparison to ARW,4 statistically insignificant difference in post hoc Conover-Iman with comparison to ABT,5 statistically insignificant difference in post hoc Conover-Iman with comparison to ACT, A-K the same letter means that the groups were homogenous in Conover-Iman post hoc comparison.…”
mentioning
confidence: 99%